2010
DOI: 10.5301/ejo.2010.2699
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Diabetic Retinopathy among Persons ≥40 Years of Age with Diabetes in Qatar: A Community-Based Survey

Abstract: Universal and periodic eye screening of patients with diabetes is recommended in Qatar. Health promotion for primary prevention and resource review are needed for early detection and management of sight-threatening DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…(1) Due to lack of proper screening and treatment facilities mainly at primary and secondary care level, many of the undiagnosed and uncontrolled diabetic patients become blind. The major risk factors for developing DR are duration of diabetes(23) and severity of hyperglycemia. (34) The diagnostic and treatment facilities are limited to urban tertiary care centers which are unable to meet the needs of entire population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Due to lack of proper screening and treatment facilities mainly at primary and secondary care level, many of the undiagnosed and uncontrolled diabetic patients become blind. The major risk factors for developing DR are duration of diabetes(23) and severity of hyperglycemia. (34) The diagnostic and treatment facilities are limited to urban tertiary care centers which are unable to meet the needs of entire population.…”
Section: Introductionmentioning
confidence: 99%
“…The major risk factors for developing DR are duration of diabetes(23) and severity of hyperglycemia. (34) The diagnostic and treatment facilities are limited to urban tertiary care centers which are unable to meet the needs of entire population. Over the last 20 years, DR has emerged as a common cause of ocular morbidity and blindness in India, moving up from number 17 (1986-1989 WHO-NPCB Survey, Government of India) to number 6 (2001–2002 NPCB national survey)(5) in the list of causes of blindness.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data for DR in the Middle Eastern countries are scarce 7 . There is considerable evidence that inflammation plays a prominent part in the pathogenesis of DR 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been seen that loss of vision due to certain types of glaucoma and cataract may be more common in people with diabetes mellitus than in those without the disease. [3] The major risk factors for developing diabetic retinopathy are the duration of diabetes [4,5] and severity of hyperglycemia. [5,6] It has been observed that visual loss or impairment due to diabetic retinopathy can be delayed by early detection, prompt treatment, and timely intervention by laser photocoagulation.…”
mentioning
confidence: 99%
“…[3] The major risk factors for developing diabetic retinopathy are the duration of diabetes [4,5] and severity of hyperglycemia. [5,6] It has been observed that visual loss or impairment due to diabetic retinopathy can be delayed by early detection, prompt treatment, and timely intervention by laser photocoagulation. [2] Diabetic retinopathy is difficult to diagnose in its early stages as it is asymptomatic, and hence, screening is the only way to identify such patients to prevent them from going blind.…”
mentioning
confidence: 99%